Understanding current practice of opioid use disorder management in emergency departments across Canada: A cross-sectional study. Issue 4 (July 2020) - Hoyeck, Patricia; Wiercigroch, David; Clarke, Cara; Moineddin, Rahim; Sheikh, Hasan; Hulme, Jennifer
ABSTRACT: Objective: Opioid-related deaths are increasing at alarming rates in Canada, with a 34% increase from 2016 to 2017. Patients with opioid use disorder often visit emergency departments (ED), presenting an opportunity to engage patients in treatment. Buprenorphine-naloxone is first-line treatment for opioid use disorder, but current management in the ED is unknown. This study aimed to characterize opioid use disorder management in the ED. Methods: We conducted a cross-sectional study of emergency physicians across Canada. A survey was circulated electronically to the Canadian Association of Emergency Physicians members. Participants were asked about their current management practices, satisfaction, and helpfulness of resources. SAS (version 9.4) was used for statistical analysis. We dichotomized Likert-scale responses to approximate relative risk ratios via a log binomial analysis. Results: The survey was completed by 179 participants for a response rate of 11.1%; 143 (79.9%) physicians treated patients with opioid use disorder more than once a week. Only 7% (n = 13) of respondents always/often gave buprenorphine in the ED. Referral to an addiction clinic where patients were seen quickly was deemed the most helpful (90.5%, n = 162). Physicians who reported satisfaction with opioid use disorder management were four times more likely to prescribe buprenorphine in the ED or as an outpatient script (RR = 4.41, CI = 2.33–8.33, p < 0.01; RR = 4.51, CI = 2.21–9.22, p < 0.01). Conclusion: This study found that buprenorphine is not frequently prescribed in the ED setting, which is incongruent with the 2018 guidelines. Care coordination and on-site support were helpful to ED physicians. Hospitals should use knowledge translation strategies to improve the care of patients with an opioid use disorder.